Comparison of ELISA and western blotting for human papillomavirus type 16 E7 antibody determination - Suchánková, Alena; Ritterová, L; Krčmář, M; Krchňák, Viktor; Vágner, J; Jochmus, I; Gissmann, L; Kaňka, Jiří; Vonka, Vladimír (Journal of general virology, 1991)
A total of 140 sera originating from healthy women and women with either cervical intraepithelial neoplasia or cervical cancer were tested for the presence of IgG antibody against E7 of human papillomavirus type 16 (HPV-16) by ELISA using a synthetic icosapeptide, denoted 16/E7-2, representing amino acids 11 to 30, and by Western blotting (WB) using a genetically engineered HPV-16 E7 fusion protein. Eighteen sera were found positive in either one or the other test. Positive reactions were more frequently detected in cervical carcinoma patients (12 of 34, 35.2%) than in the other individuals (six of 106, 5.7%). Ten children's (1 to 3 years of age) sera reacted in neither ELISA nor WB with HPV-16 E7. A high degree of concordance between the two tests was found suggesting that both tests detect the same or similar activity. To locate the reacting epitopes in the E7 protein, absorption tests were performed with peptides corresponding to various sections of the protein. Based on the results obtained, sera possessing antibody to HPV-16 E7 could be differentiated into those reactive with only the 16/E7-2 peptide and those reactive with other HPV-16 E7 epitopes.
Keywords: dospělí; Enzyme-Linked Immunosorbent Assay; Papillomavirus E7 Proteins; Female; onkogenní proteiny virové; Papillomavirus E7 - proteiny; Blotting, Western; Adult; ženské pohlaví; Papillomaviridae; lidé; nádory děložního čípku; protilátky virové; western blotting; ELISA; Oncogene Proteins, Viral; Uterine Cervical Neoplasms; lidé středního věku; Antibodies, Viral; Middle Aged; Humans